Connection between autumn Sea Surface Temperature and winter precipitation in the Iberian Peninsula - Fernández-González, Sergio
The oceanic influence on winter precipitation in the Iberian Peninsula has been evidenced in numerous scientific papers. Large-scale forecasting models generally use variables such as Sea Surface Temperature (SST), soil moisture and ice cover, but they are not very accurate yet. Using observational data, this paper analyzes the influence of North Atlantic and Mediterranean SST on winter precipitation in the Iberian Peninsula between October 1951 and September 2011. First, trends of both data sets have been calculated to study their behavior during the past six decades, showing an overall increase of SST and a substantial decrease in winter precipitation in the Iberian Peninsula, except in eastern and south-eastern regions. Then, connection patterns between autumn Sea Surface Temperature Anomalies and winter precipitation have been studied to identify ocean regions that may be used as potential predictors of winter precipitation. After applying a Principal Component Analysis to cluster the information provided by the 1431 measuring points of a SST grid with a small number of variables, the Principal Components extracted were introduced into a Multiple Linear Regression algorithm in order to obtain an estimation of winter precipitation in each river basin. The validation process has shown that the algorithm explains nearly 50% of inter-annual variability of winter precipitation in the basins of the Iberian Peninsula with a strongly oceanic influence; this percentage is somewhat lower in the Mediterranean regions.